Respuesta :
This is a vertical parabola which opens upwards
we have the general formula
(x - h)^2 = 4p(y - k) where p is the y coordinate of the focus
y/14 = x^2 - x /14 - 1/14
add 1/14 to both sides
y/14 + 1 /14 = x^2 - x /14
now complete the square
y/14 + 1/14 = x^2 - x/14 + 1/28^2
y/14 + 1/14 = (x - 1/28)^2
(x - 1/28)^2 = 1/14( y + 1)
comparing this with the general form:-
4p = 1/14
p = 1/56
so the focus is at (h,p) = (1/28, 1/56)
we have the general formula
(x - h)^2 = 4p(y - k) where p is the y coordinate of the focus
y/14 = x^2 - x /14 - 1/14
add 1/14 to both sides
y/14 + 1 /14 = x^2 - x /14
now complete the square
y/14 + 1/14 = x^2 - x/14 + 1/28^2
y/14 + 1/14 = (x - 1/28)^2
(x - 1/28)^2 = 1/14( y + 1)
comparing this with the general form:-
4p = 1/14
p = 1/56
so the focus is at (h,p) = (1/28, 1/56)
Answer:
The focus of the parabola is [tex](\frac{1}{28},-1)[/tex].
Step-by-step explanation:
The given equation is
[tex]y=14x^2-x-1[/tex]
[tex]y=14(x^2-\frac{x}{14})-1[/tex]
Add and subtract [tex](\frac{-b}{2})^2[/tex] in the equation to find the vertex form of the parabola.
[tex]y=14(x^2-\frac{x}{14}+(\frac{1}{28})^2-(\frac{1}{28})^2)-1[/tex]
[tex]y=14(x-\frac{1}{28})^2-\frac{1}{56}-1[/tex]
[tex]y=14(x-\frac{1}{28})^2-\frac{57}{56}[/tex] ... (1)
The standard equation of parabola is
[tex](x-h)^2=4p(y-k)[/tex]
Where, (h,k+p) is focus.
It can be written as
[tex]y=\frac{1}{4p}(x-h)^2+k[/tex] .... (2)
From (1) and (2), we get
[tex]h=\frac{1}{28},k=\frac{-57}{56},\frac{1}{4p}=14\Rightarrow p=\frac{1}{56}[/tex]
[tex]k+p=\frac{-57}{56}+\frac{1}{56}=\frac{-56}{56}=-1[/tex]
[tex](h,k+p)=(\frac{1}{28},-1)[/tex]
Therefore the focus of the parabola is [tex](\frac{1}{28},-1)[/tex].